Chronicling engagement: students' experience of online learning over time. Issue 2 (3rd April 2019) - Muir, Tracey; Milthorpe, Naomi; Stone, Cathy; Dyment, Janet; Freeman, Elizabeth; Hopwood, Belinda
ABSTRACT: Although there is ample research into student engagement in online learning, much of this investigates the student experience through surveys administered at a fixed point in time, usually at the exit point of a single unit of study or course. The study described in this paper, by contrast, aimed to understand online student engagement over a whole semester, guided by two overarching questions: What factors impact students' engagement over a semester? What factors account for fluctuation in engagement levels over time? This paper presents results from weekly feedback on online education students' engagement over the length of one semester at a regional Australian university. It also chronicles in more depth the experiences of one student across the same semester. The findings offer longitudinal accounts of student engagement, demonstrating that levels of engagement fluctuate and are influenced by a variety of factors.